2016
DOI: 10.1515/botcro-2016-0016
|View full text |Cite
|
Sign up to set email alerts
|

Selenium uptake and Se compounds in Se-treated buckwheat

Abstract: -In fi eld experiments, tartary buckwheat and hybrid buckwheat were foliarly sprayed with an aqueous solution of sodium selenate (20 mg Se L -1 ). In treated plants, the selenium content was signifi cantly higher than in controls, irrespective of the plant part and taxon of buckwheat. The highest average Se concentrations in hybrid and tartary buckwheat were found in seeds. The main Se species found in seeds was Semethionine. Selenium-sprayed plants had higher photochemical effi ciency of photosystem II in bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 40 publications
(56 reference statements)
0
6
1
Order By: Relevance
“…Using protease XIV and sonication assisted hydrolysis and anion exchange chromatography techniques, SeMet and Se (VI) were detected and identified in durum and bread wheat grains, and SeMet, as the principal species, accounted for 54% to 95% of the total Se content depending on the cultivars and fertilization (Galinha et al., 2015). SeMet was the only soluble Se species identified in Tartary buckwheat ( Fagopyrum tataricum ) and hybrid buckwheat ( F. hybridum ) after protease XIV hydrolysis and ion exchange chromatography, and it accounted for approximately 35% of the total Se content in grain (Golob et al., 2016). Notably, XANES spectra showed that the Se of wheat grain from a seleniferous area (Punjab, India) existed in the forms of SeMeCys (∼70%) and SeCys (∼30%), with no inorganic species detected (Eiche et al., 2015).…”
Section: Analysis Of Selenium: From Total Amount To Speciationmentioning
confidence: 99%
“…Using protease XIV and sonication assisted hydrolysis and anion exchange chromatography techniques, SeMet and Se (VI) were detected and identified in durum and bread wheat grains, and SeMet, as the principal species, accounted for 54% to 95% of the total Se content depending on the cultivars and fertilization (Galinha et al., 2015). SeMet was the only soluble Se species identified in Tartary buckwheat ( Fagopyrum tataricum ) and hybrid buckwheat ( F. hybridum ) after protease XIV hydrolysis and ion exchange chromatography, and it accounted for approximately 35% of the total Se content in grain (Golob et al., 2016). Notably, XANES spectra showed that the Se of wheat grain from a seleniferous area (Punjab, India) existed in the forms of SeMeCys (∼70%) and SeCys (∼30%), with no inorganic species detected (Eiche et al., 2015).…”
Section: Analysis Of Selenium: From Total Amount To Speciationmentioning
confidence: 99%
“…All that indicated that hybrid buckwheat had higher photosynthetic activity. Higher ETS activity in Se treated hybrid in comparison to Se treated Tartary buckwheat observed also Golob et al 2016. On the other hand, Tartary buckwheat had higher content of anthocyanins and UV-B and UV-A absorbing substances comparing to hybrid buckwheat (Fig.…”
Section: Discussionmentioning
confidence: 54%
“…It also has relatively high crude fiber content, and even more rutin and other phenolic compounds than common buckwheat (Fabjan et al 2003). Hybrid buckwheat (Fagopyrum hybridum) is a new buckwheat taxon that was recently obtained by the interspecific crossing of Fagopyrum tataricum (4x = 32) × Fagopyrum giganteum (Fesenko and Fesenko 2010), although little is known about its properties (Golob et al 2016, Golob et al 2018.…”
Section: Introductionmentioning
confidence: 99%
“…Essentiality of Se and I for plants is still under debate. However, it has been evidenced that Se has many positive effects on plants, capable of accumulating this element (Golob et al 2016). Recently there were some reports about combined effects of Se and I on plants (Zhu et al 2004, Smoleń et al 2014, 2016, Germ et al 2015, Osmić et al 2017, Jerše et al 2017.…”
Section: Vsebnost Fagopirina In Rutina V Semenih Navadne Ajde Tretiramentioning
confidence: 99%